Modelling and simulation of ZDC controlled PMSG based wind energy conversion system - Pidikiti, Tripura; Ram Das G, Tulasi (International Journal of Engineering and Technology, 2018)
This paper presents the comparison of dynamic performance and steady state operation of PMSG wind energy conversion systems with two modulation techniques. Voltage oriented control (VOC) is used for grid-connected converter along with sinusoidal pulse width modulation (SPWM) and Space Vector Modulation (SVM) schemes. The generator is controlled by using zero d- axis current (ZDC) control scheme along with optimal torque control (OTC). Performance comparison with two pulse width modulation schemes through simulation results are presented for 2MW/ 690V/ 9.75Hz Non-Salient Pole PMSG using MATLAB/SIMULINK.